Schumpeter, Sweezy, the Financial System, and Innovation: Small versus Big Business - Lambert, Thomas E.; Velardo, Tristan (Senate Hall, 2020)
Joseph Schumpeter's writings on entrepreneurship and innovation have had a profound impact on economic theory and economic thought. Schumpeter initially saw the small entrepreneur as the source of innovation and economic growth within an economic system but later saw large corporations as the source of much innovation. One of his students and friends, Paul M. Sweezy, was influenced by this thinking, and he also emphasized (along with frequent co-author Paul Baran) the role of large corporations in the U.S. and global economies. In today's times, Schumpeter would be impressed with the success of large firms regarding innovation but probably would be disappointed about the marginalization of the small entrepreneurial firm and the traditional banking system and their diminished roles in innovation. Sweezy would have predicted such an outcome as inevitable given trends in capitalist economies. This paper summarizes Schumpeter's and Sweezy's (and Baran and Sweezy's) views on how the banking system and financial markets could play a role in innovation and explains how a modern day monopoly capital system and its financial system have transformed entrepreneurship and innovation away from small business and the small entrepreneur.
Keywords: Schumpeter|Sweezy|entrepreneurship|innovation|finance|banking